Pengaruh Citra Merek Dan Kualitas Layanan Terhadap Loyalitas Pelanggan Perusahaan Otobus Rosalia Indah Transport Di Agen Perwakilan Kediri Lama - Irawan, Diska; Lidiawan, Angga Rizka; Gustiawan, Wahyu Dede (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to examine the influence of brand image and service quality on customer loyalty at Rosalia Indah Bus Company. This study was motivated by the high competition in the land transportation sector and the emergence of cases of lost passenger luggage that have the potential to affect customer trust in the company. The method applied in this study is a quantitative method with a survey approach. The object of the study was customers of Rosalia Indah Transport Company, while the sample was determined using a purposive sampling technique with the stipulation that participants were at least 20 years old and had used the service at least twice in the last six months. Data were collected using a questionnaire and analyzed using multiple linear regression. The study findings show that brand image has a positive and significant effect on customer loyalty. Service quality also has a positive and significant effect on customer loyalty. Furthermore, brand image and service quality simultaneously have a positive and significant effect on customer loyalty. These findings prove that customer loyalty is not only determined by positive brand perceptions but also by service experiences when using transportation services. The implications of this study highlight the importance of improving service quality, especially in the areas of safety, comfort, reliability, and responsiveness, as well as strengthening brand image to increase customer loyalty and maintain the company's competitive position in the land transportation sector.